2000
DOI: 10.1046/j.1440-1746.2000.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in CD95 (Fas/APO‐1)‐positive CD4+ and CD8+ T cells in peripheral blood derived from patients with autoimmune hepatitis or chronic hepatitis C with autoimmune phenomena

Abstract: These results indicate that an increase in CD4+ T cells expressing CD45RO and CD95 marks an important subset of AIH and CH-C(AI) patients. These expanded CD95+ CD45RO+ primed T cells most likely reflect a continuous antigen-specific or non-specific activation of T lymphocytes, and/or the persistent presence of activated lymphocytes as a consequence of abnormalities in the peripheral deletion of activated lymphocytes. These persistently activated lymphocytes might play a role in the induction of autoimmunity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…Possible mechanisms by which HCV increases the sensitivity of T cells to undergo apoptosis include enhancement of T-cell apoptosis as well as increasing Fas sensitivity to FasL binding on T cells, ultimately acting to tip the balance in favor of the virus [10]. This study demonstrated increased apoptosis of peripheral blood T cells which was associated with increased surface expression of Fas in patients with chronic hepatitis C, a finding similar to that reported by another study which showed that the surface expression of Fas was significantly high in T cells derived from patients with chronic hepatitis C [26]. It was found that a close relationship exists between hepatitis C virus infection of PBMCs and cell surface Fas expression in patients with hepatitis C [27].…”
Section: Discussionsupporting
confidence: 85%
“…Possible mechanisms by which HCV increases the sensitivity of T cells to undergo apoptosis include enhancement of T-cell apoptosis as well as increasing Fas sensitivity to FasL binding on T cells, ultimately acting to tip the balance in favor of the virus [10]. This study demonstrated increased apoptosis of peripheral blood T cells which was associated with increased surface expression of Fas in patients with chronic hepatitis C, a finding similar to that reported by another study which showed that the surface expression of Fas was significantly high in T cells derived from patients with chronic hepatitis C [26]. It was found that a close relationship exists between hepatitis C virus infection of PBMCs and cell surface Fas expression in patients with hepatitis C [27].…”
Section: Discussionsupporting
confidence: 85%
“…1 The involvement of CD8ϩ lymphocytes in the pathogenesis of AIH is increasingly be coming obvious. 9,10 It appears that swift and extensive damage to hepatocytes in the initial stage of AIH would be mediated by CTL through the major histocompatibility (MHC) class 1 pathway. As AIH becomes full-blown, hepatitis would tend to be mediated by helper T cells through the MHC class 2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Taya et al [33] demonstrated a close relationship between HCV infection of PBMCs and cell-surface Fas expression, as well as the possibility of PBMC apoptosis via the Fas-mediated system. Expression of Fas on PBMCs was also significantly increased in these patients [15,34].…”
Section: Discussionmentioning
confidence: 79%
“…It is characterized by a number of distinct morphological alterations accompanied by biochemical features including DNA fragmentation and membrane alterations with exposure of phosphatidyl serine on the outside of the plasma membrane [14]. Fas receptor on the cell membrane is a determinant of apoptosis in normal lymphocytes, and abnormalities in its expression might contribute to the severity of hepatocyte inflammation [15] .…”
Section: Introductionmentioning
confidence: 99%